Kuktem gets 10 Gigabit Ethernet network - Computerworld Malaysia, staff (2003)
Avaya recently deployed the first fully operational 10 Gigabit Ethernet network, which was installed at the University College of Engineering and Technology Malaysia (KUKTEM) in Kuantan. This is presently the first and only true converged site which uses complete Avaya offerings including a 10 Gigabit Ethernet LAN, Wi-Fi, and IP telephony.